Pengaruh Strategi Problem Based Learning Terhadap Hasil Belajar Pendidikan Agama Islam Siswa - Risma Rahayu; Sulaiman Sulaiman (An-Nuha, 2022)
This research is motivated by the low learning outcomes of Islamic Religious Education for Class X Students at SMK Negeri 2 Padang. This study aims to determine (1) the implementation of the Problem Based Learning Strategy, (2) the learning outcomes of Islamic Religious Education Students, (3) how much influence the Problem Based Learning strategy has on the learning outcomes of Islamic Religious Education students in class X at SMK Negeri 2 Padang. This type of research is quantitative research using correlational research methods. Data was collected by means of observation, questionnaires, and documentation. Data analysis used simple linear regression analysis, with Problem Based Learning strategy as the independent variable and student learning outcomes of Islamic Religious Education as a test variable using the SPSS version 25 program assistance. The data were tested using simple linear regression test, t test, f, and test coefficient of determination. The results showed that there was an influence between the Problem Based Learning strategy on the learning outcomes of students' Islamic religious education.